Effect of wind turbulence on wind ballistic trajectory of a medium calibre weapon system - Knight, Daniel (Cranfield University, 2023)
Current ballistics and Fire Control Systems (FCS) use the assumption that crosswind located at the firing point will be constant between firing point and target location. The single constant crosswind value is then used to calculate the ballistic drift offset required to correctly engage a target at range and maintain an accurate firing solution. Variations in crosswind speed and direction are not considered by FCS but are known to cause drift errors in flight and offset the resulting impact point, the error is commonly known as gustiness. Applying a variable crosswind drift correction for both time of flight and projectile height could produce an improved result by considering variations in the crosswind dynamics. Using multiple crosswind sensors at difference heights, a wind gradient curve can be produced to model wind turbulence and speed variations in reference to the projectile trajectory height. Similarly, changes in the crosswind can be modelling against the engagement timeline to show gustiness in relation to the time of flight of the projectile. The accuracy and performance of the new ballistic model can be measured against the NATO standard coincidence window, which is used to evaluate FCS accuracy. The NATO error window of 0.3 mrads can be used to measure the probability of hit between the current constant crosswind and the new variable crosswind FCS model (US Army Aberdeen Test Center, 2009b). Using a reference tank target at a nominal distance of 2,000 meters, gives a coincidence window requirement of 60 cm square located on target centre mass. The thesis found for the reference projectile used, a 40CTAS 40 mm round (CTA International, 2018b), that the FCS accuracy could be improved by 10.95% when including variations in the crosswind. The probability of hit inside the NATO coincidence window is improved to 56.16% when using crosswind at the instant of firing, compared to holding a single constant value during the engagement timeline. It was also found that dynamic crosswind conditions can be included and modelled into a Point Mass Ballistic Model. Variations in the crosswind gradient curve can be used to assess turbulence and change in wind conditions. The wind gradient curve also demonstrates that wind conditions are not constant in relation to both time and height above ground, during an engagement sequence.
Goyder, Hugh - Associate Supervisor Helliker, Aimee - Associate Supervisor
Keywords: Ballistics; Meteorological wind; Fire Control (FC); Fire Control Systems (FCS); Gun System Control (GSC); Armoured Fighting Vehicles (AFV); Trajectory and coincidence